Karakteristik dan Komponen Perangkat Pembelajaran Dalam Menilai Pencapaian Tujuan Pendidikan di SMPN 1 Sawoo - Widi Nailil Asna Audianingrum (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Learning evaluation is an important element in the education system to measure student success and the effectiveness of the teaching and learning process. This study explores the characteristics of learning evaluation tools used at SMPN 1 SAWOO through a descriptive qualitative approach. This research describes the validity, reliability, relevance and representation of evaluation tools in supporting the achievement of learning objectives. The evaluation carried out covers the cognitive, affective and psychomotor domains, and utilizes objective and non-objective test instruments. The research results show that the evaluation tool used meets the practical, discriminatory and specific aspects, so it is able to provide an overview of students' overall abilities. In addition, evaluation helps educators identify student needs, provide remedial programs, and improve the quality of learning on an ongoing basis. It is hoped that these findings can contribute to the development of evaluation tools that are more integrated and adaptive to today's educational needs.